Muş Bridges in The Ottoman Archive Documents - Şen, Korkmaz (Istanbul Universitesi, 2019)
Muş, located in the Eastern Anatolia Region, has hosted a number of civilizations throughout history. That Muş was situated particularly on the western route of the Urartian state and on a historical trade route, made the city remain in a strategical location throughout history. The bridges examined in the study were also on the mentioned route. However, it may be stated that the route had been used by all states ruling the region in the interlude until the rule of the Ottoman Empire. Four historical bridges, including the Mus Ulu Bridge, the Karasu Bridge, the Malazgirt Bridge and the Abdurrahman Pasha Bridge have reached the present day. However, among them, no archival information about the Abdurahman Pasha Bridge could be obtained. Similarly, although the archival information related to the Mus Karasu Bridge is available, the bridge itself did not survive. There is no exact information indicating when and by whom the analyzed bridges were first built. It may be inferred from the obtained archive documents that the historic bridges in Muş were either rebuilt or substantially repaired because they had been too destroyed to cross in the late Ottoman period. In the existing publications, the studied bridges were dated back to the Seljuk period, when they were examined in terms of their materials, engineering, and plans. However, any documents confirming this assumption could not be obtained. The aim of the study is to evaluate the existing documents in particular and the bridges, in terms of their materials, engineering, and plans. © 2019 The Author(s).
Osmanlı Arşiv Belgelerinde Muş Köprüleri
Keywords: Abdurrahman Paşa; Bridge; Kırkgöz; Murat; Muş